Preparing the Arabic Language Teacher for Non-Native Speakers, Following the Experience of the Arabic Language Institute at the International University of Africa: منى يوسف محمَّد وقيع الله (Journal of the College of Education for Women, 2020)
The study aims to examine the reality of preparing the Arabic language teacher for non-native speakers by presenting the experience of the Arabic Language Institute at the International University of Africa. Thus, it addresses the following questions: How is it possible to invest the long scientific experiences in proposal and experiment preperations to qualify Arabic language teachers for non-native speakers? What is the reality of preparing an Arabic language teacher at the Institute? How did the Arabic Language Institute process teacher preparation? What are the problems facing the preparation of the Arabic language teachers and the most important training mechanisms used in that Institute?What problems faced the implementation of the experiment of preparing an Arabic language teacher at the language Institute? To present the experiment, the study used the descriptive method. The study is important for program planners of higher education studies, course designers, and for people interested in teaching strategies and teacher training. It also provides Arabic language teachers for non-native speakers to diploma institutions. The study has found that the university experiment is distinguished as it adopts the practical track to form the cumulative experience that helps to solve teacher preparation problems.